2015
DOI: 10.2134/agronj14.0480
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal Fluctuation of Soil Carbon Dioxide Emission in Differently Managed Pastures

Abstract: Soil carbon dioxide emission (ECO2) is a process determined by biotic and abiotic factors in uenced by land use and management practices. In grassland ecosystems, grazing intensity may a ect C input from plants into soil, and thus may also change soil respiration rate. Indeed, limited information is available regarding the e ects of grazing management on ECO2. is study was conducted to evaluate ECO2 seasonal variation, and its relationship to soil temperature (Tsoil) and precipitation, in an area with di erent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
17
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 22 publications
(30 reference statements)
4
17
0
Order By: Relevance
“…The lower ECO 2 on the first day after planting are explained in part by the low soil moisture, approximately 0.135 m 3 m -3 in both experiments. After this, rainfall increased ECO 2 with a slight decrease in soil temperature (under 32 °C), suggesting soil moisture was a driving factor of an increase in microbial activity as supported by the finding (Brito et al, 2015). Conversely, when soil moisture is adequate for microbial growth, soil temperature could be an important factor for controlling soil respiration (Carbone et al, 2011).…”
Section: Eco 2 Soil Temperature and Soil Moisturementioning
confidence: 60%
See 1 more Smart Citation
“…The lower ECO 2 on the first day after planting are explained in part by the low soil moisture, approximately 0.135 m 3 m -3 in both experiments. After this, rainfall increased ECO 2 with a slight decrease in soil temperature (under 32 °C), suggesting soil moisture was a driving factor of an increase in microbial activity as supported by the finding (Brito et al, 2015). Conversely, when soil moisture is adequate for microbial growth, soil temperature could be an important factor for controlling soil respiration (Carbone et al, 2011).…”
Section: Eco 2 Soil Temperature and Soil Moisturementioning
confidence: 60%
“…Furthermore, irregular rainfall and dry winters hinder the addition of C since the growth of cover crops is impaired and the amount of plant residues produced in the off-season may be reduced (Castro et al, 2015). However, cover crop residues left on the soil surface can decrease the soil temperature, and retain soil moisture and eventually ECO 2 (Brito et al, 2015;Carbone et al, 2011). ECO 2 also depends on the crop rotations used in the agricultural system, which are affected by the quality of crop residue left on the soil and the amount of easily mineralizable C (Kögel-Knabner, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Soil moisture and air temperature are important environmental factors controlling soil CO 2 flux, but soil temperature has been consistently more strongly correlated with CO 2 flux from grassland soils than soil moisture (Liebig et al, ; Brito et al, ; Rong et al, ). In our study, soil CO 2 flux was positively correlated with both soil moisture and air temperature, but was more strongly correlated with air temperature.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, better pasture management allowing for an ideal plant height would probably promote greater pasture yields as a result of higher water availability. Additionally, Brito et al () showed that CO 2 –C emissions were lower with increasing pasture height as a result of Brachiaria pasture management.…”
Section: Discussionmentioning
confidence: 99%